Measurement and instrumentation principles - Morris, Alan S., 1948- (Butterworth-Heinemann, 2001)
'Measurement and Instrumentation Principles' is the latest edition of a successful book that introduces undergraduate students to the measurement principles and the range of sensors and instruments that are used for measuring physical variables. Completely updated to include new technologies such as smart sensors, displays and interfaces, the 3rd edition also contains plenty of worked examples and self-assessment questions (and solutions). In addition, a new chapter on safety issues focuses on the legal framework, electrical safety and failsafe designs, and the author has also concentrated on RF and optical wireless communications. Fully up-to-date and comprehensively written, this textbook is essential for all engineering undergraduates, especially those in the first two years of their course. Completely updatedIncludes new technologies such as smart sensors and displays.